O zjawisku, które w tekstach polskich występuje w ponad 60% wyrazów - Mańczak, Witold (Poznańskie Spotkania Językoznawcze, 2015)
The present writer believes that in all languages the form of words depends on three main factors, not only on regular sound change and analogical development, but also on what he calls irregular sound change due to frequency. He has analysed a fragment of a poem by Mickiewicz and has found different reduced forms there, e. g. waść < wasza miłość, mości < miłościwy, mego < mojego, dość < dosyć, już < OPol. juże, mi < mnie, przed (a reduced equivalent of przód), co (a reduced equivalent of OCS. česo), bez (a reduced equivalent of Biez‑ in the toponym Biezdziedza), za (a reduced equivalent of Lith. ažúo), ‑em < OPol. jeśm, ‑sz (a reduced equivalent of the OCS. ending ‑ši), ‑eś < OPol. jeś, ‑ą < PSl. *‑ętь, ‑ć < OPol. ‑ci, ‑ę < PIE. *‑omi or adjectival endings like ‑emu < *‑u‑jemu, ‑y < *‑ъ‑jь, ‑ej < *‑y‑jejě, ‑ego < *‑a‑jego, ‑e < *‑y‑jě. These irregular reductions, which are very numerous, occur in texts in more than 60% of words. There are six arguments which prove that there exists a connection between irregular phonetic reductions and frequency of use. Finally, the present writer quotes the opinion of a statistician according to which there is less than a chance in 10 million that this connection does not exist.